DEVELOPING ENGLISH LISTENING SONGS MATERIAL BASED ON SCIENTIFIC APPROACH FOR THE TENTH GRADE STUDENTS OF SMAS IMELDA MEDAN - Liza Muharina Bayazid; Sumarsih Sumarsih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2023)
The objective of this study as to develop an appropriate English listening songs material based on Scientific Approach for grade tenth. This study was carried out at SMAS Imelda Medan. This research was conducted by using Research and Development (R&D) method. The research of Research and Development which contained six stages; gathering information and data, analysing data, designing materials, validating new materials by expert, revising materials based on expert suggestion, and final product. The data was gathered through the distribution of questionnaire for students and interviewed an English Teacher and students to get the student’s need. The study’s conclusion resulted in the development of the English listening songs material E-Book, which may be used as a learning material for students to learn English listening songs. The product has been validated by two experts in percentage terms, the average score of expert validation was 91.4% in linguistic aspect, the process aspect was 94.2%, the content aspect was 93%, and the layout was 92%. The average score was 93% which was categorized as very good and it was suggested to use in English class especially for English listening songs at Senior High School level.